2013
DOI: 10.1088/0004-637x/766/1/45
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Interaction of Shocks With Small Interstellar Clouds as a Pre-Stage to Star Formation

Abstract: Cloud compression by external shocks is believed to be an important triggering mechanism for gravitational collapse and star formation in the interstellar medium. We have performed MHD simulations to investigate whether the radiative interaction between a shock wave and a small interstellar cloud can induce the conditions for Jeans instability and how the interaction is influenced by magnetic fields of different strengths and orientation. The simulations use the NIRVANA code in three dimensions with anisotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
4
21
0
Order By: Relevance
“…While the outer layers of the clouds evaporate due to thermal conduction, the cores are stretched into dense and cold filaments, as was also found by Mellema et al (2002), Fragile et al (2004), Orlando et al (2005), and Johansson & Ziegler (2013). The simulations show how a conductive interface forms, leading to an increased density in the core that manages to radiate the energy conducted into the cloud, while stabilizing the cloud against hydrodynamical instabilities.…”
Section: Discussion and Summarysupporting
confidence: 52%
“…While the outer layers of the clouds evaporate due to thermal conduction, the cores are stretched into dense and cold filaments, as was also found by Mellema et al (2002), Fragile et al (2004), Orlando et al (2005), and Johansson & Ziegler (2013). The simulations show how a conductive interface forms, leading to an increased density in the core that manages to radiate the energy conducted into the cloud, while stabilizing the cloud against hydrodynamical instabilities.…”
Section: Discussion and Summarysupporting
confidence: 52%
“…Bruggen & Scannapieco (2016) include both radiative cooling and heat conduction in simulations of clouds being ejected in galactic outflows. They find that while the outer envelope is evaporated, the central region cools and stretches into dense filaments (in agreement with simulations that only include radiative cooling: Mellema et al 2002;Fragile et al 2004;Orlando et al 2005;Johansson & Ziegler 2013). These clouds are accelerated only at early times because their cross-section decreases dramatically as the outer layers evaporate, so they move more slowly than simulated clouds without heat conduction.…”
Section: Missing Physicssupporting
confidence: 63%
“…In addition, hydrodynamic instabilities are strongly suppressed with nearequipartition magnetic fields β ∼ 1 (e.g., Mac Low et al 1994;Fragile et al 2005;Shin et al 2008). Calculations of shock-cloud interactions including magnetic fields, anisotropic thermal conduction, and radiative cooling by Orlando et al (2008) have shown that magnetic fields with moderate strength (β = 4) indeed suppress heat transfer and hydrodynamic instabilities (see also Johansson & Ziegler 2013). In future work, it will be interesting to extend the SNR expansion simulations of this paper to include magnetic fields and anisotropic conduction, in order to quantify possible changes in the momentum injection, maximum mass of hot gas, and other basic properties.…”
Section: Multiple Sne and Superbubbles/galactic Winds -mentioning
confidence: 99%